1997
DOI: 10.1074/jbc.272.44.27818
|View full text |Cite
|
Sign up to set email alerts
|

rRNA Maturation as a “Quality” Control Step in Ribosomal Subunit Assembly in Dictyostelium discoideum

Abstract: In Dictyostelium discoideum, newly assembled ribosomal subunits enter polyribosomes while they still contain immature rRNA. rRNA maturation requires the engagement of the subunits in protein synthesis and leads to stabilization of their structure. Maturation of pre-17 S rRNA occurs only after the newly formed 40 S ribosomal particle has entered an 80 S ribosome and participated at least in the formation of one peptide bond or in one translocation event; maturation of pre-26 S rRNA requires the presence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Since this structure lacks initiator tRNA, it was proposed that it is not engaged in translation and that its disassembly would be required before 40S mRNA binding, reassembly, and productive translation initiation (Strunk et al 2012). Earlier studies in Dictyostelium discoideum had reached a similar conclusion but had more radically proposed that 18S maturation occurs as in Escherichia coli primarily after 80S formation, possibly at the first translation initiation stage (Mangiarotti et al 1997;Shajani et al 2011). Therefore, although for many years it has been assumed that incomplete 18S processing prevents nuclear subunits from associating, there is now abundant evidence that the 40S subunit containing 20S pre-rRNA can interact with 60S.…”
Section: Introductionmentioning
confidence: 67%
“…Since this structure lacks initiator tRNA, it was proposed that it is not engaged in translation and that its disassembly would be required before 40S mRNA binding, reassembly, and productive translation initiation (Strunk et al 2012). Earlier studies in Dictyostelium discoideum had reached a similar conclusion but had more radically proposed that 18S maturation occurs as in Escherichia coli primarily after 80S formation, possibly at the first translation initiation stage (Mangiarotti et al 1997;Shajani et al 2011). Therefore, although for many years it has been assumed that incomplete 18S processing prevents nuclear subunits from associating, there is now abundant evidence that the 40S subunit containing 20S pre-rRNA can interact with 60S.…”
Section: Introductionmentioning
confidence: 67%
“…This possibility is strengthened by the observation that in normally growing cells, Nob1, Fap7, and a small amount of the 20S pre-rRNA cosediment with 80S ribosomes but not with polyribosomes (6 and this work). Furthermore, Dictyostelium discoideum preribosomes are often detected in 80S monosomes and even polyribosomes in vivo and in vitro (31,32). In this organism, the assembly of immature ribosomal subunits into polyribosomes is an obligatory step, and it has been shown that if newly formed ribosomes cannot function in translation, late rRNA maturation steps do not take place (31).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, it is conceivable that 20 to 18 S rRNA processing might occur after 40 S-60 S subunit joining or even after the first round of translation. In Dictyostelium, only 40 S subunits that are capable of translation undergo the final rRNA processing step, providing a precedent (51).…”
Section: Discussionmentioning
confidence: 99%